How do tennis players control their balance during the serve? - Jamkrajang, P.; Robinson, M. A.; Limroongreungrat, W.; Vanrenterghem, J. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate how postural balance is manifested in high level tennis players, and whether movement variability is phase dependent. Twelve experienced tennis players (8 males and 4 females; age 21.5±4.11 years; height 174.75±6.06 cm; body mass 66.83±8.12 kg) completed 10 tennis successful serves. Whole-body kinematics were recorded and whole-body extrapolated centre of mass trajectories calculated. Within-subject variation was presented temporally to evaluate phase-dependent differences. Overall, our results showed individual balance control preferences and a progressive increase of within-subject variability throughout the serve movement. This knowledge will help trainers and coaches identify learning and performance needs associated to whole-body balance control.